Pengaruh Literasi Keuangan Syariah, Financial Efficacy, Financial Attitude, Financial Behavior Terhadap Kepuasan Finansial - Uni Sasti Hadiah; Esy Nur Aisyah (Jurnal Ekonika : Jurnal Ekonomi Universitas Kadiri, 2022)
This study discusses the influence of Islamic Financial Literacy, Financial Efficacy, Financial Attitude, Financial Behavior on Financial Satisfaction in Economics Faculty Students of UIN Maulana Malik Ibrahim Malang with the number of respondents to be analyzed as many as 95 students. Researchers used multiple linear regression analysis which was carried out using SPSS.20 software. With the conclusion, in this study the results showed that simultaneously Islamic financial literacy, financial efficacy, financial attitude, financial behavior had an effect on financial satisfaction. Partially, Islamic financial literacy, financial attitude, and financial behavior have an influence on financial satisfaction, while financial efficacy has no effect on financial satisfaction.